Generation Differences in the Behaviour of Household Consumers in Romania Related to Voluntary Measures to Reduce Electric Energy Consumption - Cosmina-Simona Toader; Ciprian Ioan Rujescu; Andrea Feher; Cosmin Salasan; Lavinia Denisia Cuc; Karoly Bodnar (Amfiteatru Economic, 2023)
The Ukraine crisis, the sharp increase in the price of electricity and the excessive dependence of the European Union countries on fossil fuels from Russia have led to a series of actions in the direction of energy saving, clean energy production and diversification of energy sources. The REPoweEU plan, through related financial and legal measures, aims to build a new infrastructure and a new energy system at the EU level. The reduction of energy consumption represents an important orientation of this plan, and in this context, the present study investigates, based on a questionnaire, the behaviour of consumers (households) in Romania towards voluntary measures to reduce electricity energy consumption and identify the behavioural differences between four generations: Baby Boomers, X, Y, and Z. The analysis of the results was performed using ANOVA and Tukey statistical tests, using the SAS Studio software application. The results highlight some differences in the behaviour of generations and the patterns regarding the approach to behavioural integration for responsible energy consumption. The work is useful because it outlines the attitude and behaviour of Romanian consumers toward the national and European objectives of reducing energy consumption, energy waste, and increasing the share of alternative energy sources.
Keywords: D10; L94; P18; Q28; 330; REPowerEU; ANOVA; Tukey; sustainable behaviour; generations